Motivating LIS Professionals for Developing Skill in Digital Environment (INDIAN JOURNAL OF VOCATIONAL EDUCATION, 2022)
Motivation is the art of influencing people, a kind of encourage incentives whenever encourage a person to do work which is for the betterment of the society. As a storehouse of knowledge library and its professional always have to provide up-to-date and ICT basedservice towards its user. A skilled LIS professional always be needed to fulfill user query. So, it is very important to motivate them for develop their skill towards their job. In this research article factors which motivate the LIS professionals and promote their skills arediscussed.